Infliximab use in the Netherlands: Uptake and characteristics of originator and biosimilars over time. Issue 4 (24th October 2021) - Overbeek, Jetty A.; Kuiper, Josephina G.; Bakker, Marina; van den Bemt, B. J. F. ( Bart); Herings, Ron M. C.
Abstract : Aims: The objective of this retrospective cohort study was to provide an overview of the utilization of originator and biosimilar infliximab in the Netherlands. Methods: All infliximab dispensings were selected from the PHARMO In‐patient Pharmacy Database from 2002–2018. Descriptive analyses were performed in order to characterise initiators and to describe switching patterns over time. Results: Overall, 3840 patients with 61 274 infliximab dispensings were identified. 2496 patients initiated an originator infliximab and 777 patients initiated a biosimilar infliximab. Overall, 57% of the patients was female and mean age was 43.2 years. Both originators and biosimilars were mostly prescribed by gastroenterologists, followed by internists and rheumatologists. After market authorisation of the first biosimilar, the proportion of new patients initiating the biosimilar increased from 39% in 2015 to 91% in 2018. Out of 704 patients eligible for switching 34% switched. Among switchers, the proportion of females was 60% and mean age at index was 45.1 years. Among nonswitchers, 55% were female and mean age was 39.8 years. The median time to switch was 1.7 years and switchers were most frequently initiated on infliximab by a rheumatologist (42%), while nonswitchers were most frequently initiated by a gastroenterologist (42%). Conclusion: The results of this large population‐based cohort show an increase in biosimilar initiation in daily clinical practice. The number of switchers remains relatively low as nonmedical switch is not encouraged in the Netherlands. Abstract :